ANTIOXIDANT ACTIVITIES OF EXTRACTS FROM THE LEAVES AND STEM BARKS OF Artocarpus scortechinii KING (Jurnal Teknologi (Sciences & Engineering), 2015)
The antioxidant activities of extracts (n-hexane, dichloromethane, ethyl acetate and methanol) from the leaves and stem barks of Artocarpus scortechinii were evaluated using various biochemical assays. The quantification of the Total Antioxidant Capacity was measured using ferric reducing antioxidant potential (FRAP) and 2,2'-azino-bis(3-ethyl-benzothiazoline-6-sulphonic acid) (ABTS) assays. While, the qualitative of The Total Phenolic Content (TPC) was determined via standard gallic acid calibration graph which was expressed as mg gallic acid equivalent (GAE)/g of dry weight (dw) using Folin Ciocalteau’s reagent. Among all the extracts tested, the methanolic extract of the stem barks showed the highest phenolic content with TPC value of 136.84 mg GAE/g dry weight (dw). FRAP results were expressed as mM equivalent to FeSO4.7H2O by calculating from the standard FeSO4.7H2O calibration graph. The ethyl acetate extract of the stem barks showed the most significant reducing potential in the range between 0.27-2.47 mM FRAP. ABTS+˙ radical scavenging capacity showed that the ethyl acetate extract of the stem barks had the highest scavenging capacity at concentration 1.0 mM with percentage of 90.9%.
Keywords: Artocarpus; Artocarpus scortechinii; antioxidant activities